Mycorrhiza-mediated recruitment of complete denitrifying Pseudomonas reduces N2O emissions from soil - Li, Xia; Zhao, Ruotong; Li, Dandan; Wang, Guangzhou; Bei, Shuikuan; Ju, Xiaotang; An, Ran; Li, Long; Kuyper, Thomas W.; Christie, Peter; Bender, Franz S.; Veen, Ciska; et al. (Microbiome, 2023)
BackgroundArbuscular mycorrhizal fungi (AMF) are key soil organisms and their extensive hyphae create a unique hyphosphere associated with microbes actively involved in N cycling. However, the underlying mechanisms how AMF and hyphae-associated microbes may cooperate to influence N2O emissions from “hot spot” residue patches remain unclear. Here we explored the key microbes in the hyphosphere involved in N2O production and consumption using amplicon and shotgun metagenomic sequencing. Chemotaxis, growth and N2O emissions of isolated N2O-reducing bacteria in response to hyphal exudates were tested using in vitro cultures and inoculation experiments.ResultsAMF hyphae reduced denitrification-derived N2O emission (max. 63%) in C- and N-rich residue patches. AMF consistently enhanced the abundance and expression of clade I nosZ gene, and inconsistently increased that of nirS and nirK genes. The reduction of N2O emissions in the hyphosphere was linked to N2O-reducing Pseudomonas specifically enriched by AMF, concurring with the increase in the relative abundance of the key genes involved in bacterial citrate cycle. Phenotypic characterization of the isolated complete denitrifying P. fluorescens strain JL1 (possessing clade I nosZ) indicated that the decline of net N2O emission was a result of upregulated nosZ expression in P. fluorescens following hyphal exudation (e.g. carboxylates). These findings were further validated by re-inoculating sterilized residue patches with P. fluorescens and by an 11-year-long field experiment showing significant positive correlation between hyphal length density with the abundance of clade I nosZ gene.ConclusionsThe cooperation between AMF and the N2O-reducing Pseudomonas residing on hyphae significantly reduce N2O emissions in the microsites. Carboxylates exuded by hyphae act as attractants in recruiting P. fluorescens and also as stimulants triggering nosZ gene expression. Our discovery indicates that reinforcing synergies between AMF and hyphosphere microbiome may provide unexplored opportunities to stimulate N2O consumption in nutrient-enriched microsites, and consequently reduce N2O emissions from soils. This knowledge opens novel avenues to exploit cross-kingdom microbial interactions for sustainable agriculture and for climate change mitigation.Video Abstract